2011
DOI: 10.1017/s0033291711001310
|View full text |Cite
|
Sign up to set email alerts
|

Familial influence and childhood trauma in female alcoholism

Abstract: Background To assess the role of genetic and environmental factors in female alcoholism using a large population-based twin sample, taking into account possible differences between early and late onset disease subtype. Method Twins aged 20–47 years from the Swedish Twin Registry (n = 24 119) answered questions to establish lifetime alcohol use disorders. Subjects with alcoholism were classified for subtype. Structural equation modeling was used to quantify the proportion of phenotypic variance due to genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 41 publications
8
39
1
2
Order By: Relevance
“…Exposure to alcohol before 6 years approximately doubles the likelihood of reporting frequent, heavy or problem drinking during adolescence (Fergusson, Lynskey, & Horwood, 1994). Not only do parental drinking behaviours increase risk of developing problematic alcohol behaviours (Eve 1989), but also violence between parents, particularly violence initiated by the father (Fergusson & Horwood, 1998), and maltreatment and abuse as a child (Gilbert et al, 2009;Magnusson et al, 2011). Taken together, these studies suggest that permissive attitudes to alcohol in the home environment, as well as violence or trauma in the home, may increase the likelihood of later development of problem drinking behaviours (Fergusson, Boden, & Horwood, 2008).…”
Section: Judgments From Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to alcohol before 6 years approximately doubles the likelihood of reporting frequent, heavy or problem drinking during adolescence (Fergusson, Lynskey, & Horwood, 1994). Not only do parental drinking behaviours increase risk of developing problematic alcohol behaviours (Eve 1989), but also violence between parents, particularly violence initiated by the father (Fergusson & Horwood, 1998), and maltreatment and abuse as a child (Gilbert et al, 2009;Magnusson et al, 2011). Taken together, these studies suggest that permissive attitudes to alcohol in the home environment, as well as violence or trauma in the home, may increase the likelihood of later development of problem drinking behaviours (Fergusson, Boden, & Horwood, 2008).…”
Section: Judgments From Othersmentioning
confidence: 99%
“…Not only has trauma early in life been identified as a risk factor for alcohol-related problems (Gilbert et al, 2009;Magnusson et al, 2011), alcohol-use disorders with an onset later in life may be triggered by an unpleasant or traumatic event in adulthood (Johnson, 2010;Sacks & Keks, 1998). Alcohol abuse has been associated with disaster, exposure to grotesque death, physical and sexual abuse in adulthood, and combat in military service (reviewed in Stewart, 1996).…”
Section: Judgments From Othersmentioning
confidence: 99%
“…As discussed in the literature review, major factors that contribute to alcohol abuse include past and current physical, emotional, and psychological trauma including CSA, stress, environmental surroundings, family history (Magnusson et al, 2012;Enoch, 2011;Hughes et al, 2007;Kilpatrick et al, 2000). Additionally, prior research has shown that there is a correlation between women who were abused during childhood and contracting HIV, with alcohol being implicated in this association (Schacht et al, 2009).…”
Section: Discussion Of Findings: Research Questionsmentioning
confidence: 99%
“…Alcohol use accounts for 5.1% of the global burden of disease, suggesting that it accounts for as many deaths and disability as tobacco and hypertension (WHO, 2015;Room, Babor, & Rehm, 2005;Krug, 2002). Alcohol use also has farreaching impact that contribute to public endangerment, such as drunk driving that leads to accidental injuries, domestic violence, fetal alcohol syndrome, neuropsychological impairment, poor medication adherence, economic and loss of productivity, and psychiatric comorbidity (CDC, 2015;Magnusson et al, 2012;Brady & Back, 2012;Enoch, 2011;Hasin, Stinson, Ogburn, & Grant, 2007;Room, Babor, & Rehm, 2005;Cook, 1998). In an effort to combat alcoholism, advocates and interventionists have developed partnerships and programs to assist individuals struggling with alcohol dependence that are split into three general categories: brief intervention, specialized treatment programs, and mutual help groups (Molina, Gardner, Souza-Smith, Whitaker, 2014;Room, Babor, & Rehm, 2005).…”
Section: Alcohol Abusementioning
confidence: 99%
See 1 more Smart Citation